Hubungan Tempat Bersalin, Penolong Persalinan dan Peran Tenaga Kesehatan terhadap Kelengkapan Imunisasi Dasar pada Masa Pandemi Covid-19 - Fajirin Alam Syah (Jurnal Syntax Admiration, 2025)
Immunization is the most effective primary prevention against infectious diseases. Immunization protects individuals from serious illnesses and prevents the spread of infectious diseases. In Indonesia, every baby is required to receive complete basic immunization according to the immunization schedule issued by the Indonesian Pediatrician Association (IDAI). The Ministry of Health noted a decrease in the number of complete basic immunization coverage in March-April 2020 and the same period in 2019. There was almost a 4.7% difference in the percentage of complete immunization coverage in 2019 and 2020. This figure experienced a decline after complete basic immunization coverage in January-2020. February 2020 was stated to have increased from the same period in the previous year (CNN Indonesia, 2020). This research was conducted using an analytical observational method with a cross sectional research design. The total research sample was 139 respondents and the sampling technique used a total sampling technique. Based on the Chi squere test, there is a relationship between place of delivery (p-Value 0.00 < 0.05) and completeness of basic immunization during the Covid-19 pandemic in the working area of the Parigi Health Center, there is a relationship between birth attendants (p-Value 0.00 < 0.05) and the role of health workers (p-value 0.026 < 0.05) with complete basic immunization. For the Parigi health center, it is recommended that health workers develop more promotive and preventive programs and provide assistance to traditional birth attendants so that all births are under the supervision of health workers.